2017
DOI: 10.1016/j.athoracsur.2016.09.107
|View full text |Cite
|
Sign up to set email alerts
|

Two Decades of Lung Retransplantation: A Single-Center Experience

Abstract: Lung ReTx outcomes are significantly worse than for primary transplantation but may be appropriate in well-selected patients with certain diagnoses. Lung ReTx in patients older than 50 years or within 2 years of primary lung transplantation was associated with decreased survival. Further work is warranted to identify patients who benefit most from ReTx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 26 publications
(54 reference statements)
2
16
0
Order By: Relevance
“…Visual inspection of the survival curves strongly suggests a difference, which would be consistent with prior data in which retransplantation has consistently been associated with poorer overall survival compared to primary transplant with a median survival of only 2.5 years compared to 5.7 years . A recent study from the University of Florida found similar results, with a median survival of 2 years in patients transplanted at their center between 1995 and 2014, with similar findings noted with respect to worse survival in patients retransplanted within 2 years of primary and in those with restrictive CLAD . The Hannover group has previously reported supportive findings as well, noting poorer survival in non‐BOS indications for transplant (acute failure or airway issues) .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Visual inspection of the survival curves strongly suggests a difference, which would be consistent with prior data in which retransplantation has consistently been associated with poorer overall survival compared to primary transplant with a median survival of only 2.5 years compared to 5.7 years . A recent study from the University of Florida found similar results, with a median survival of 2 years in patients transplanted at their center between 1995 and 2014, with similar findings noted with respect to worse survival in patients retransplanted within 2 years of primary and in those with restrictive CLAD . The Hannover group has previously reported supportive findings as well, noting poorer survival in non‐BOS indications for transplant (acute failure or airway issues) .…”
Section: Discussionsupporting
confidence: 81%
“…and 2014, with similar findings noted with respect to worse survival in patients retransplanted within 2 years of primary and in those with restrictive CLAD. 24 The Hannover group has previ- and that primary transplant recipients who died were not eligible or did not survive to retransplant. As such, the control group is inherently biased, and this must be born in mind when interpreting the comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…Our results provide strong evidence that lung retransplantation for CLAD is an effective strategy, with acceptable short-and mid-term outcomes comparable with those of primary LTx. Our results are similar to other published and registry data reviews demonstrating similar long-term outcomes [3,[13][14][15][16][17]. This is an important finding that illustrates the dramatic improvement of retransplantation outcomes over the past two decades [18][19][20].…”
Section: Commentsupporting
confidence: 90%
“…52 Although the exact mechanisms for this latter observation are not known, it has been hypothesized that increased abundance of donor hematopoietic cells could play an active role in the maintenance of tolerance or that the increased burden of foreign tissue could result in immune anergy. 52 Regarding retransplantation, survival remains inferior compared with primary transplantation 53,54 but, according to the 2014 ISHLT report, primary LTx and retransplant recipients have similar ACR rates between discharge and 1-year follow-up. 54 Ex-vivo lung perfusion (EVLP) is being increasingly applied in clinical practice, not only to alleviate organ shortage but also to assess, and potentially improve, function of marginal lungs.…”
Section: Donor Characteristicsmentioning
confidence: 99%